A Leadership of Refusal: Remaking the Narrative of the Falling Leader - Bell, Emma; Sinclair, Amanda; Vachhani, Sheena J. (British journal of management, 2024)
The metaphor of the glass cliff is used to describe patterns whereby women are more likely to be selected for challenging leadership positions that have a higher risk of failure. This paper explores how the glass cliff metaphor contributes to a narrative of woman's fall that individualizes a leader's responsibility to avoid risks that may lead to failure. As an alternative, we introduce the leadership of refusal as a feminist resource for remaking the narrative of woman's fall. Refusal is understood as an embodied political and ethical stance that declines to recognize, rather than resists or simply opposes, masculine leadership norms. Through analysis of how three women leaders were represented by the media, former Australian Prime Minister, Julia Gillard, former Australian of the Year, Grace Tame, and climate change activist, Greta Thunberg, we analyse key moments of refusal where these leaders breached the masculine order through their embodied performances. We argue that leadership of refusal enables an understanding of how women leaders exercise power in agentic, non‐sacrificial ways. We therefore urge leadership researchers to position refusal centrally, because first saying no in order to take risks towards achieving transformative action is, we suggest, a defining feature of leadership.